Welcome to the Inaugural Issue For Our New Chief Editor - Neale Fong (Asia Pacific Journal of Health Management, 2022)
Welcome to the inaugural issue of the College’s flagship journal with our new Editor-in-Chief, Dr Mark Avery. On behalf of all members, contributors and readers we wish him and the editorial team all the best.